Exploitation of Inland-Breeding Antarctic Petrels by South Polar Skuas - Brooke, Michael de L; Keith, Dave; Røv, Nils (Oecologia, 1999)
During the austral summer of 1996/1997 we studied south polar skuas at Svarthamaren, Dronning Maud Land, Antarctica, where the world's largest known colony of Antarctic petrels is found. Our censuses suggested approximately 250 full-grown skuas and 140,000 breeding pairs of petrels were present. During their breeding season, skuas did not visit the open sea at least 200 km from the site; they relied entirely on prey caught and scavenged from the petrel colony. Because the site is so isolated, we asked whether the prey (petrels) had swamped the predators (skuas), or whether there was evidence that predator numbers were limited by the size of the prey population. Particularly at the end of the petrel incubation period, we found a close correspondence between the energy required by adult skuas and their chicks, ascertained from time budget studies, and the rate at which petrel eggs disappeared from the colony. This suggests that, in this closed system, the predator population was limited by the prey population, and that predator swamping was not an advantage that petrels gained by nesting in this remote location.
Publisher: Springer
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

The influence of ornithogenic products on the nutrient status of soils surrounding nests on nunataks in Dronning Maud Land, Antarctica - Cocks, Martin P; Harris, Jean M; Steele, William K; Balfour, Dave A (Polar Research, 1999)
Keywords: Dronning Maud Land; fugler; nunataker; næringsstoff; ornitologi; petreller

Studies of seabirds at Svarthamaren - Tveraa, Torkild; Andreassen, Cecilie; Christensen, Guttorm N (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; fugler; ornitologi; petreller

Distribution and Abundance of the Antarctic Petrel - van Franeker, J. A.; Gavrilo, M.; Mehlum, Fridtjof; Veit, R. R.; Woehler, E. J. (Waterbirds: The International Journal of Waterbird Biology, 1999)
Published and unpublished information on the distribution and abundance of the Antarctic Petrel (Thalassoica antarctica) is reviewed. Currently 35 colonies with approximately half a million breeding pairs are known. All but one of these known colonies are situated in East Antarctica. However, an estimate derived from at sea studies in three of four apparent centers of oceanic occurrence suggests a population as high as four to seven million breeding pairs (10 to 20 million individuals). In spite of the tentative nature of such an estimate, the difference with the colony-derived figure strongly suggests the existence of large, currently undiscovered colonies, particularly in western Antarctica and Victoria Land, where a complete mismatch exists between bird observations at sea and known colonies. In eastern Antarctica, in addition to undiscovered colonies, some known ones could be considerably larger than currently documented.
Publisher: Waterbird Society
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; petreller; zoologi

On the cost of reproduction in long-lived birds: the influence of environmental variability - Erikstad, Kjell Einar; Fauchald, Per; Tveraa, Torkild; Steen, Harald (Ecology, 1998)
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Diet and prey consumption of Antarctic petrels Thalassoica antarctica at Svarthamaren, Dronning Maud Land, and at sea outside the colony - Lorentsen, Svein-Håkon; Klages, Norbert; Røv, Nils (Polar Biology, 1998)
The diet of the Antarctic petrel Thalassoica antarctica was studied during two seasons at Svarthamaren, an inland colony in Dronning Maud Land, Antarctica, and in the pack ice off the coast of Svarthamaren. The most important food (wet mass) at Svarthamaren was crustaceans (67%), fish (29%) and squid (5%); however, individuals collected in the pack ice took mostly fish (87%). The prey composition and lengths of prey are comparable to what has been documented in other studies on this species. Estimates of food consumption by birds breeding at Svarthamaren (ca. 250,000 pairs) suggest that approximately 6500 tonnes of crustaceans, 2800 tonnes of fish and 435 tonnes of squid are consumed during the breeding season. The annual consumptions of these birds are estimated to be 34,100 tonnes of crustaceans, 14,700 tonnes of fish, and 2300 tonnes of squid. Satellite telemetry data indicate that Antarctic petrels from Svarthamaren may fly more than 3000 km during one foraging trip, and thus may cover a huge ocean area to obtain their prey.
Keywords: Dronning Maud Land; NARE 1991/92; NARE 1993/94; fugler; ornitologi; petreller; zoologi

Regulation of food provisioning in the Antarctic petrel; the importance of parental body condition and chick body mass - Tveraa, Torkild; Sether, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Journal of Animal Ecology, 1998)
1. Two hypotheses may explain how long-lived seabirds regulate the food provisioning to their chick. The fixed level of investment hypothesis states that the parents provide food for their chick according to an intrinsic rhythm, independent of their chick's need. The flexible investment hypothesis states that the parents adjust their food provisioning both according to their chick's and their own need. 2. We tested how the Antarctic petrels adjust the food-provisioning according to their own body condition or to their chick's need. First, we selected parents in poor and good body condition. Then we gave all parents randomly a chick of different body mass, but of the same age. We then measured the chicks daily until they were fed for the first time after swapping. 3. Parents in good body condition at hatching were more likely to produce a chick that was still alive 9 days after hatching than parents in poor body condition. Chick body mass at day 9 and at the end of the guarding period was positively related to the mean body condition of the parents at hatching. 4. The meal size provided by parents in good body condition was larger than that provided by parents in poor body condition. Parents in good body condition delivered more food to small than to large chicks, whereas no such relationship was found among parents in poor body condition. 5. Our results suggest that the Antarctic petrel parents adjust the amount of food delivered to their chick according to both the chick's need and their own body condition, and that the ability to respond to the chick's need is dependent upon their own body condition.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Body mass and parental decisions in the Antarctic petrel Thalassoica antarctica : how long should the parents guard the chick? - Tveraa, Torkild; Sæther, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Behavioral Ecology and Sociobiology, 1998)
In Procellariiformes, the parents guard the chick after it has attained homeothermy. This strategy may reduce the probability that a small chick is taken by predators, but is costly as only one parent can forage at a time. The decision to leave the chick may therefore be a compromise between the chick's vulnerability to predators, the body condition of the parent on the nest and whether the foraging parent returns in time. We studied how the number of days that parents guarded the chick was related to the body mass of the parent at the nest and the time the foraging parent spent at sea in the Antarctic petrel Thalassoica antarctica. We also examined how the body mass of the parent on the nest and the duration of the foraging trips influenced the chicks' body condition at the end of the guarding period. When the foraging parent did not return to the nest in time to relieve its mate, the number of days the parent on the nest kept guarding the chick was positively related to its body mass on arrival in the colony. The number of days the foraging parent spent at sea was positively related to the body mass of its mate, but those that returned in time had a shorter stay at sea relative to their mate's body mass than those that did not return before their mate had left. Apparently, both the body mass of the parent at the nest and the ability of the foraging parent to adjust its stay at sea to the mate's body mass is important for the number of days the parents guard the chick and also the chick's body condition at this point. The inability to return to the nest before the mate has left may be the result of needing a minimum amount of time at sea to find food, or because some parents having low foraging success and therefore prolong their stay at sea.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Breeding biology and diet of pintado petrels Daption capense at Bouvetøya during the summer of 1996/97 - Huyser, Onno; Dyer, Bruce M; Isaksen, Kjell; Ryan, P; Cooper, J (Commission for the Conservation of Antarctic Marine Living Resources, 1997)
Pages: [13 s.] Publication Title: Working Group on Ecosystem Monitoring and Management Place: Hubbs-Sea World Research Institute, San Diego, USA
Keywords: Bouvetøya; ornitologi; petreller; reproduksjon; zoologi

Studies of seabirds and seals at Bouvetøya 1996/97 - Isaksen, Kjell; Hofmeyr, Greg; Dyer, Bruce M; Huyser, Onno; Næstvold, Alf (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Bouvetøya; NARE 1996/97; fugler; ornitologi; seler; zoologi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Size-Dependent Variation in Reproductive Success of a Long-Lived Seabird, the Antarctic Petrel (Thalassoica Antarctica) - Sæther, Bernt-Erik; Lorentsen, Svein-Håkon; Tveraa, Torkild; Andersen, Reidar; Pedersen, Hans Christian (The Auk, 1997)
We examined how variation in parental quality influences the reproductive success of a long-lived seabird, the Antarctic Petrel (Thalassoica antarctica). In particular, we focused on how quality of parents can interact with and influence the effects of stochastic variation in the environment due to varying climatic conditions. Large annual variation was found in reproductive success. However, body mass of individual chicks at the end and be ginning of the nestling period was strongly correlated in two of the study years, suggesting consistent variation among parents in their ability to feed offspring. Furthermore, chick mass was related both to overall body size and to body mass of their parents. Short brooding-shift intervals also were important for growth and survival of chicks. The probability of chick survival to the age of 30 days (ca. two weeks before fledging) was strongly correlated with chick mass when the chick was left unattended. However, the relative importance of different parental characteristics differed between years. These results show that reproductive success of the Antarctic Petrel is influenced by stochastic variation in the environment, probably re lated to climatic conditions. Effects of this stochastic variation may depend on body mass and/ or body condition of the parents.
Full-text: https://sora.unm.edu/sites/default/files/journals/auk/v114n03/p0333-p0340.pdf
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1991/92; NARE 1992/93; fugler; ornitologi; petreller; zoologi

Regulation of foraging trips and costs of incubation shifts in the Antarctic petrel (Thalassoica antarctica) - Tveraa, Torkild; Lorensten, Svein-Håkon; Sæther, Bernt-Erik (Behavioral Ecology, 1997)
In species where incubation is shared by both parents, the mate's ability to fast on the nest may constrain the time available for foraging. The decision to return to the nest should therefore be a compromise between an animal's own foraging success and its mate's ability to fast on the nest. To examine how the body conditions of incubating Antarctic petrels, Thalassoica antarctica, influence both the length of foraging trips and incubation shifts, we experimentally handicapped females by increasing their flight costs during a foraging trip by adding lead weights to their legs. Handicapped females spent more time at sea and had lower body conditions at arrival to the colony than controls, and, moreover, females in poor body condition at arrival to the colony spent generally more time at sea than those with higher body condition. The prolonged time period spent at sea by handicapped females was associated with higher desertion rates than among controls. The time the incubating mates fasted increased with their body condition at arrival to the colony, suggesting that a high body condition of the incubating bird may reduce the probability of nest desertion. Accordingly, our results suggest that the time spent foraging is adjusted to the body conditions of both the foraging and incubating mate.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Effects of Egg Size and Parental Quality on Early Nestling Growth: An Experiment with the Antarctic Petrel - Amundsen, Trond; Lorentsen, Svein-Hakon; Tveraa, Torkild (Journal of Animal Ecology, 1996)
A large number of studies have reported a positive relationship between the egg size of birds and the subsequent growth and/or survival of nestlings, but such effects may partly be due to confounding variables, e.g. parental quality. In order to evaluate the potential effects of egg size, and of parental quality, on early nestling growth in the Antarctic petrel, we performed an experiment in which eggs of different size were swapped between nests. 2. From a sample of 300 nests with eggs of known size, we selected eggs belonging to the lower quartile (small eggs), and those belonging to the upper quartile (large eggs), with respect to volume. Half of the small eggs were exchanged with small eggs from other nests, and the other half with large eggs. A similar procedure was used for large eggs. Growth and survival of the nestlings were recorded until 12 days old. 3. Hatching success was positively related to egg size. 4. Egg size influenced nestling body mass until the age of 3 days, and tarsus length was affected until 12 days old. However, these effects were not due to an effect of egg size on growth rates, but reflected instead the influence of egg size on hatchling size. 5. In contrast to most previous studies, we found no effect of parental quality (as reflected in the size of own eggs) on foster nestling size or growth until 12 days old. This could be because egg size does not reliably reflect parental quality in the species, or because parental effects become evident only at later nestling stages. 6. We discuss why egg size variation is maintained in this and other species where egg size influences parental fitness through the survival of eggs or nestlings.
Publisher: [Wiley, British Ecological Society]
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Regulation of Food Provisioning in the Antarctic Petrel Thalassoica antarctica - Lorentsen, Svein-Håkon (Journal of Animal Ecology, 1996)
1. Life-history theory predicts that individual birds should invest in reproduction according to their current body condition and the future prospects for survival and reproduction. Thus, it could be expected that current adult body condition should significantly influence food provisioning rates, food loads and concurrent chick growth in the Antarctic petrel. 2. In order to study the significance of parental body condition I correlated meal sizes, feeding frequencies and chick growth with the body condition of the parents. 3. There was a strong correlation between the average meal size delivered to a chick and its growth rate. Adult body condition at the time of hatching was strongly correlated with the average size of meals delivered to individual chicks. Male and female body condition at the time of hatching and average body condition of the pair at the first incubation shift and at hatching significantly influenced the body mass of the chick on day 30. Male body condition and the average body condition of the pair correlated significantly with the growth rate of the chick. 4. The difference in body mass at the age of 30 days of chicks from parents with good body condition compared with chicks from parents with poorer body condition was nearly double that expected. 5. The results strongly suggest that the effort spent during the chick-rearing period, and thus reproductive success, is regulated by the body condition of the parents.
Publisher: [Wiley, British Ecological Society]
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Seabird research at Svarthamaren during NARE 1993/94 - Lorentsen, Svein-Håkon; Amundsen, Trond; Røv, Nils; Tveraa, Torkild (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi

Report of the Norwegian Antarctic Research Expedition 1993/94 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1996)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1993/94; geodesi; glasiologi; ornitologi

Egg Size and Early Nestling Growth in the Snow Petrel - Amundsen, Trond (The Condor, 1995)
I studied egg size variation, and the influence of egg size on early nestling growth, in Snow Petrels Pagodroma nivea breeding at Svarthamaren, Dronning Maud Land, Antarctica (71 degrees 53'S, 5 degrees 10'E). Egg sizes ranged from 36.4 to 52.1 cm(3), with a mean of 44.9 cm(3). Hatching occurred during 16-24 January, with a median hatching date of 20 January. Egg size had a significant effect on the body mass of hatchlings, explaining 30% of the variation in body mass of nestlings hatched within the last 24 hr, and 58% of the body mass variation of nestlings weighed while still slightly wet. An experiment, which included swapping of eggs between nests, together with analyses of non-manipulated nests, revealed an effect of egg size on nestling body masses at ages of two and four days. From the experiment, no effect of maternal quality as expressed by her egg size could be found. At an age of four days, 40% of the nestlings were left alone in the nest by their parents. Nestlings not attended by a parent at this age were significantly lighter than were those with parental company. Parents that had left their young by the time these were four days old may have been poor quality birds, as indicated by the tendency for such birds to have laid smaller eggs than had those still tending their young at the same nestling age.
Publisher: American Ornithological Society
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Regulation of parental investment in the Antarctic petrel Thalassoica antarctica: an exchange experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Polar Biology, 1995)
An experiment was conducted on the Antarctic petrel to test whether the parents were able to respond to changes in food demand of their offspring. Two experimental groups were formed by replacing eight 20-day-old chicks with 10-day-old chicks, and vice versa. The growth rate of chicks in the experimental groups was compared with that in two control groups with chicks of known age. The growth rate of 10-day-old chicks in the nests of parents which initially had 20-day-old chicks did not differ significantly from that in their respective control groups. This indicates that those parents were able to raise a new young nestling, despite having already raised another chick from hatching to 20 days. However, the 20-day-old chicks placed in nests with 10-day-old chicks had a significantly lower growth rate than their control group. Feeding rate per day and nest did not differ significantly among any of the groups. This suggests that the observed difference in growth rate between 20-day-old chicks is related to a lower amount of food delivered per visit to experimental chicks. Thus, in the Antarctic petrel, the feeding rate apparently is not regulated by the status of the chick, but by the parents' ability to gather food or willingness to provide food for the chicks.
Keywords: Dronning Maud Land; NARE 1989/90; fugler; ornitologi; petreller; zoologi

Incubation and brooding performance of the Antarctic Petrel Thalassoica antarctica at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils (Ibis, 1995)
Antarctic Petrel Thalassoica antarctica incubation and brooding effort was studied at Svarthamaren, Dronning Maud Land, during the austral summer of 1991-1992. The females probably left the nest site shortly after egg laying. The duration of incubation and brooding shifts as well as the daily weight loss (absolute and proportionate) were comparable with those of other similar-sized procellariform species. Males spent more time incubating and brooding than did females, suggesting higher female energy stress due to egg laying, Incubating birds which were below average weight were likely to desert the nests before their mates returned from feeding trips. Both males and females lost approximately one-fifth of their body-weight during their first incubation shifts. Nevertheless, they increased their initial weights from egg laying to hatching and had their highest initial weights when they returned to start the shift during which the egg hatched. No factors related to adult body-weight explained the duration of the incubation shifts, Both males and females gained weight at a higher rate when at sea than they lost it during incubation, and it is suggested that factors unrelated to food availability or individual feeding skills may be important in regulating the duration of the incubation shifts and the stay at sea.
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Sex determination of Antarctic Petrels Thalassoica antarctica by discriminant analysis of morphometric characters - Lorentsen, Svein-Håkon; Røv, Nils (Polar Biology, 1994)
We present data on sexual dimorphism in some morphological measurements (wing length, head length, bill depth and bill length) in the Antarctic Petrel Thalassoica antarctica. Males were on average larger than females for all measurements. Sexual dimorphism was on average largest for bill depths whereas wing lengths discriminated least between the sexes. A discriminant function including bill depth, head length and wing length correctly sexed 92% of the sample. Due to between-measurer variation it is recommended that morphometric measurements obtained by others on sexed birds are compared with ours before proceeding with the use of the discriminant function on unsexed individuals.
Keywords: Dronning Maud Land; NARE 1991/92; biodiversitet; fugler; ornitologi; zoologi; økologi

Report of the Norwegian Antarctic Research Expedition 1991/1992 - Østerhus, Svein (ed.) (Norsk Polarinstitutt, 1994)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1991/92; fugler; geologi; glasiologi; ornitologi; oseanografi

Seabird studies at Svarthamaren, Dronning Maud Land - Røv, Nils; Lorentsen, Svein-Håkon; Bangjord, Georg (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi

Regulation of parental effort in a long-lived seabird an experimental manipulation of the cost of reproduction in the antarctic petrel, Thalassoica antarctica - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Behavioral Ecology and Sociobiology, 1993)
The fitness of a parent in an altricial bird species is likely to be a function of the proportion of resources allocated to offspring production in relation to the amount spent on its own survival. Here we report an experiment on the Antarctic petrel in which we manipulated the costs of rearing an offspring by placing small lead loads on the legs of one parent. The bird could then either decrease its own body reserves or reduce the food load to the chick. The manipulated birds decreased their food load and increased the feeding interval, compared with unmanipulated birds. Consequently, the rate of chick loss increased. No significant difference was found between the body weights of experimental and control birds during the experiment.
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi; økologi

Fugle-og selundersøkelser på Bouvetøya i desember/januar 1989/90 - Bakken, Vidar (Norsk Polarinstitutt, 1991)
Publication Title: Meddelelser
Keywords: Bouvetøya; biologi; fugler; fugleregistreringer; ornitologi; pingviner; seler; zoologi

Thermoregulatory abilities in chicks of the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (Polar Biology, 1991)
We studied the thermoregulatory capacity of Antarctic Petrel chicks, Thalassoica antarctica, breeding in a large colony in Queen Maud Land (71-degrees-53'S, 5-degrees-10'E) on the Antarctic continent. Compared to newly hatched chicks of other birds, those of the Antarctic Petrel are characterized by a relatively high standard metabolic rate (SMR) and thermal conductance. Their metabolic scope is limited, however, being only 1.6 times the SMR, and they consequently depend on parental brooding to maintain T(b). At an age of 11 days the chicks become thermally independent and are left alone in the nest. The chicks keep a relatively high body temperature (> 36-degrees-C) throughout their early development and we found no indication that they normally experience hypothermia. A significant positive relationship between latitude of breeding and SMR of the hatchlings is shown to exist for procellariiform birds. It is suggested that the high SMR found in Antarctic Petrel hatchlings could be a prerequisite for achieving a high growth rate, rather than being of any thermoregulatory significance.
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; petreller; zoologi

Foraging economics and performance of polar and subpolar Atlantic seabirds - Croxall, John P; Briggs, Dirk R (Polar Research, 1991)
Keywords: Antarktis; fugler; næring; ornitologi; pingviner; zoologi; økologi

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

Antarktispetrellen: på grensen av det mulige - Sæther, Bernt-Erik (Naturen, 1991)
Keywords: Dronning Maud Land; fugler; ornitologi

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L (Polar Research, 1990)
Keywords: Antarktis; fugler; ornitologi; polarområdene; zoologi

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Navigation to nest site in the snow petrel (Pagodroma nivea) - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (The Condor, 1988)
Publisher: American Ornithological Society
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Census of breeding Antarctic petrels Thalassoica antarctica and physical features of the breeding colony at Svarthamaren, Dronning Maud Land, with notes on breeding snow petrels Pagodroma nivea and south polar skuas Catharacta maccormicki - Mehlum, Fridtjof; Gjessing, Yngvar; Haftorn, Svein; Bech, Claus (Polar Research, 1988)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Breeding ecology of the Antarctic petrel Thalassoica Antarctica in Mühlig-Hofmannfjella, Dronning Maud Land - Fridtjof, Mehlum; Claus, Bech; Svein, Haftorn (Proceedings of the NIPR Symposium on Polar Biology, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Interrelationships between egg dimensions, pore numbers, incubation time, and adult body mass in Procellariiformes with special reference to the Antarctic petrel Thalassoica antarctica - Mehlum, Fridtjof; Rahn, Hermann; Bech, Claus; Haftorn, Svein (Polar Research, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Ornithological investigations in Mühlig-Hofmannfjella, Dronning Maud Land - Mehlum, Fridtjof; Bech, Claus; Haftorn, Svein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi

Observations on the snow petrel (Pagodroma nivea) in Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Dronning Maud Land; fugler; ornitologi; zoologi

What is "Mumiyo" from Antarctica - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1967, 1967)
Keywords: Dronning Maud Land; ekspedisjoner; farmakologi; fugler; ornitologi; zoologi

Nyere iakttagelser over fuglelivet på Bouvetøya - Heintz, Natascha (Norsk Polarinstitutt. Årbok 1961, 1962)
I «Informasjons-bulletin for den sovjetiske Antarktisekspedisjon», nr. 13, (1959) har G. A. SOLJANIK publisert en liten artikkel om fuglelivet på Bouvetøya. Da forfatteren har vært i land nær Kapp Circumcision hvor det tidligere, så vidt jeg kan bringe i erfaring, ikke har vært foretatt noen landing, kan det kanskje være av interesse å referere noen av de opplysningene han kommer med, ikke minst da det på en interessant måte utvider vårt kjennskap til fuglefaunaen på denne ugjestmilde øya.
Keywords: Bouvetøya; fugler; ornitologi

Fugl i norske biland. - 2. Bouvet-øya - Holgersen, Holger (Sterna, 1960)
Publisher: Museet Place: Stavanger
Keywords: Bouvetøya; fugler; ornitologi; zoologi

The snow petrel Pagodroma nivea nesting in Dronning Maud Land - Løvenskiold, Herman L. (Ibis, 1960)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Ornithology of the "Brategg" Expedition - Holgersen, Holger (Hvalfangstmuseet, 1957)
Publication Title: Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48
Keywords: Brategg ekspedisjon; Peter I. Øy; fugler; ornitologi

Range of the Ringed Penguin, Pygoscelis antarctica - Holgersen, Holger (The Auk, 1951)
Publisher: American Ornithological Society
Keywords: Brategg ekspedisjon; Peter I. Øy; fugler; ornitologi

Den antarktiske fugleverden - Holgersen, Holger (Naturen, 1944)
Keywords: Antarktis; fugler; ornitologi

Experimental investigations on the respiratory function in diving mammals and birds - Scholander, P F (I kommisjon hos Dybwad, 1940)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Antarktis; marin biologi; marin zoologi; ornitologi; pingviner